Pemberian Penyuluhan Kesehatan Infeksi Menular Seksual Terhadap Pengetahuan Remaja di SMA Swasta Kota Bandung - Liliek Fauziah; Anna Karolina; Treesia Sujana (STIKES Ngesti Waluyo, 2025)
The prevalence of sexually transmitted infections, such as AIDS, suffered by adolescents aged 15-19 years old, males, was as high as 46 adolescents in Bandung City in 2022. There are several ways to reduce the risk of sexually transmitted infections, including abstaining from sexual activity, using condoms, reducing the frequency of intercourse, practicing monogamy, and choosing partners who are not much different in age. Therefore, there is a need to do health education about sexually transmitted infections. The purpose of the study was to investigate the impact of providing health education about sexually transmitted infections on the knowledge of adolescents at a private high school in Bandung. The study used a quantitative approach. The type of research is a pre-experimental design with a One-Group Pre-Test Post-Test design. The respondents’ study were 142 adolescents in grades XI and XII of a private high school in Bandung, selected using a proportional stratified random sampling technique. The research instrument utilized PowerPoint and a questionnaire that had been tested for validity, yielding a validity coefficient of 0.361, which can be considered valid. The data analysis used was the Wilcoxon Signed Rank Test. The results of the study showed that at the pre-test, more than half of the respondents had a good level of knowledge (50.7%), and at the post-test, almost all respondents had a good level of knowledge (94.4%). The results of the Wilcoxon Signed Rank Test obtained a significance value of p-value <0.001 (p-value<0.05), which showed that there was an effect of education on sexually transmitted infection health in adolescents at SMA Nasional Bandung. As a suggestion, the private high schools in Bandung are expected to provide additional learning about sexually transmitted infections in adolescents.